A technical assessment of water supply quality in three local government areas of Lagos State, Nigeria - Ogedengbe, K.; Ilupeju, S. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
The study was carried out to assess the technical problems associated with the sources, quality and quantity of drinking water supplies in Agege, Ifako/Ijaiye and Alimosho Local Government Areas (LGAs) of Lagos State, Nigeria. It was also conducted to find out the extent of water contaminations, from various sources, being consumed by residents of the LGAs studied and also to proffer solutions to reduce their effects. Households participation was involved it was revealed that about 35% of respondents use borehole, 25% obtained water from communal taps and 16% from well water. Individual house tap accounted for 11%, 9% from water vendors and 4% of the respondents employed water tankers. Chlorination was the most employed treatment technique while few others boil water before drinking. An average of 50 litres was the water use per capita. 50-100 meters was obtained as the average distance between respondents’ residence and water sources. The survey showed that some of these sources were sited near soakaways, some co-existing with tombs, dirty drains and water logged environment. Twelve water samples were examined for analysis on chemical and biological properties. Results obtained however showed that all chemical properties analyzed are within recommended standards for drinking water. Salmonella spp. was also not detected in any of the samples.